Molded all-silicon beta molecular sieve as well as preparation method and application thereof
By combining dry adhesive conversion and seed crystal method, a molded all-silicon β molecular sieve without binder was prepared, which solved the problems of high cost and low strength, achieved an efficient and low-cost preparation process, and improved the adsorption performance and mechanical strength of the product.
Patent Information
- Application Number
- CN202311287388.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2025-04-08
AI Technical Summary
The existing molded all-silicon β-molecular sieve has problems such as high cost, low strength, and is not conducive to industrial amplification.
The adhesive-free all-silicon β molecular sieve was prepared by dry-adhesive conversion and seed crystal method, and mechanical strength was obtained through the interlaced growth of crystals, and the preparation cost was reduced by adjusting the addition of silicon source and template agent.
It realizes efficient preparation of adhesive-free molded all-silicon β molecular sieve. The product has a large specific surface area, excellent adsorption performance and good mechanical strength, which reduces the preparation cost and is suitable for industrial applications.
Smart Images

Figure CN119774632A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of molecular sieves, and in particular relates to a formed all-silicon beta molecular sieve and a preparation method and application thereof. Background Art
[0002] Molecular sieves are a type of inorganic microporous crystalline materials, which are widely used in catalysis, adsorption separation, ion exchange and other fields. The main synthesis methods include hydrothermal synthesis, dry gel conversion, solvent-free synthesis, seed-assisted synthesis, microwave-assisted synthesis, etc. Among them, dry gel conversion, solvent-free method and seed-assisted method can reduce the use of solvent or template in the crystallization process, thereby reducing costs and three wastes.
[0003] Molecular sieve products prepared by conventional methods are generally in powder form. Molecular sieves need to be washed and filtered after crystallization. Molecular sieves in powder form are relatively difficult to filter, and nano-scale molecular sieves are even more difficult to filter due to their small crystal size. When molecular sieves in powder form are used as fixed bed catalysts or adsorbents, inert binders need to be added to form them so that they have a certain mechanical strength. However, binders generally reduce the specific surface area of catalysts or adsorbents and reduce active sites. The preparation of binder-free molecular sieves can solve the above two problems at the same time.
[0004] All-silicon β molecular sieve has certain acidity and hydrophobicity, and has broad application prospects in catalysis, adsorption, etc., and nano-level β molecular sieve has a larger surface area and a shorter diffusion path than micron molecular sieve. The most common method is the hydrothermal synthesis method with the addition of fluoride ions. The addition of fluoride ions requires the treatment of fluoride-containing wastewater. On the other hand, the yield of the hydrothermal synthesis method is relatively low, and more three wastes are discharged, which increases the preparation cost of zeolite molecular sieves.
[0005] CN101863490A discloses a method for synthesizing small-grained all-silicon beta zeolite, in which a silicon source, a fluoride ion source, a tetraethylammonium hydroxide source and water are mixed into a mixture, and then a crystallization reaction is performed to obtain an all-silicon zeolite with a grain size of less than 5 microns. The method requires a relatively large molar ratio of TEAOH. + / SiO2 molar ratio needs to be between 0.3 and 1.0, and a large amount of F is added - , and the micron-sized grains described in the patent are relatively large.
[0006] CN101757889A discloses a BEA type binder-free hydrophobic high-silicon zeolite adsorbent and a preparation method thereof, wherein the method uses sodium-type BEA type zeolite with a silicon-aluminum molar ratio of 5-300 as a raw material, adds an amorphous silica gel binder, then de-crystallizes and inorganic acid dealuminates, and finally performs high-temperature steam hydrophobic treatment to obtain the BEA type binder-free hydrophobic high-silicon zeolite adsorbent. The method requires steps such as secondary crystallization, acid dealuminates and steam treatment, and the preparation process is complicated, which increases the preparation cost.
[0007] CN113636566A discloses a synthesis process of all-silicon Beta molecular sieve and its preparation process. The method adopts a liquid phase synthesis mode, and tetraethylammonium hydroxide, silicon source, carbon nanotubes and ethanol are added to a crystallization solution to finally obtain an all-silicon Beta molecular sieve. The specific surface area of the molecular sieve product prepared by the method is partially provided by carbon nanotubes, and the amount of template added in the process is large, and the cost is relatively high.
[0008] CN115991483A discloses a β zeolite molecular sieve and a preparation method thereof, wherein an alkali source, an aluminum source, and a tetraalkylamine are mixed, and then the precursor is dried and crystallized to obtain a high-silicon β zeolite molecular sieve. However, the specific surface area and pore volume of the zeolite molecular sieve obtained by this method are smaller than those of the conventional β zeolite molecular sieve (the specific surface area of the conventional β zeolite molecular sieve is about 600m 2 / g), and the mechanical strength of the obtained product is not high.
[0009] CN108264056A discloses a method for synthesizing all-silicon Beta zeolite molecular sieves by a sodium-free and solvent-free route. The method places a silicon source, a quaternary ammonium base and all-silicon seed crystals in a mortar, grinds them, and then places them in a reactor for crystallization, suction filtration, and drying to obtain all-silicon Beta molecular sieve raw powder. The method synthesizes all-silicon Beta molecular sieve raw powder at a relatively low cost, but when it is loaded into a fixed bed as an adsorbent or catalyst, a binder still needs to be added to provide a certain mechanical strength.
[0010] In summary, the existing shaped all-silicon β molecular sieve still has the problems of high cost, low strength, and being unfavorable for industrial scale-up. Therefore, it is still necessary to develop a new preparation method of the shaped all-silicon β molecular sieve. Summary of the invention
[0011] In view of the problems existing in the prior art, the present invention provides a molded all-silicon beta molecular sieve and a preparation method thereof. The molded all-silicon beta molecular sieve obtained by the preparation method of the present invention belongs to a binder-free molecular sieve, and the product itself has a certain mechanical strength through the staggered growth of crystals, has a flaky structure, small grains and a large specific surface area, and a large specific surface area is conducive to adsorption. The flaky structure can enhance the diffusion performance inside the molecular sieve, so that the molded all-silicon beta molecular sieve of the present invention has excellent performance in the treatment of volatile organic compounds.
[0012] In a first aspect, the present invention provides a shaped all-silicon beta molecular sieve, wherein the crystals of the shaped all-silicon beta molecular sieve have a flaky morphology, and the crystal size is less than or equal to 300nm, and the specific surface area of the shaped all-silicon beta molecular sieve is 550m 2 / g-750m 2 / g.
[0013] In some embodiments, the crystal size of the formed all-silicon β molecular sieve is 20nm-300nm, for example, 20nm-250nm, 20nm-200nm, 20nm-150nm, 30nm-100nm, 30nm-300nm, 30nm-250nm, 30nm-200nm, 30nm-150nm, 30nm-100nm, 50nm-300nm, 50nm-250nm, 50nm-200nm, 50nm-150nm, 50nm-100nm or a range of any other value therebetween.
[0014] In some embodiments, the crystal thickness of the formed all-silicon beta molecular sieve is less than or equal to 50 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm or 45 nm.
[0015] In some embodiments, the size of the crystal length direction of the shaped all-silicon β molecular sieve is 20nm-300nm, for example, 20nm-250nm, 20nm-200nm, 20nm-150nm, 30nm-100nm, 30nm-300nm, 30nm-250nm, 30nm-200nm, 30nm-150nm, 30nm-100nm, 50nm-300nm, 50nm-250nm, 50nm-200nm, 50nm-150nm, 50nm-100nm or a range of any other value therebetween.
[0016] In some embodiments, the size of the crystal width direction of the shaped all-silicon β molecular sieve is 20nm-300nm, for example, 20nm-250nm, 20nm-200nm, 20nm-150nm, 30nm-100nm, 30nm-300nm, 30nm-250nm, 30nm-200nm, 30nm-150nm, 30nm-100nm, 50nm-300nm, 50nm-250nm, 50nm-200nm, 50nm-150nm, 50nm-100nm or a range of any other value therebetween.
[0017] In some embodiments, the microstructure of the formed all-silicon beta molecular sieve is a sheet-like structure and / or a staggered-growing sheet-like structure.
[0018] In some embodiments, the shaped all-silicon β molecular sieve is a shaped all-silicon β molecular sieve having a flaky microstructure, wherein the grain size of the shaped all-silicon β molecular sieve is the average length of the flaky microstructure.
[0019] In some embodiments, the flaky microstructure of the formed all-silicon beta molecular sieve has a length of 50 nm to 300 nm and a width of 50 nm to 300 nm.
[0020] In some embodiments, the thickness of the flaky microstructure of the formed all-silicon β molecular sieve is 10 nm to 50 nm.
[0021] In some embodiments, the micropore volume of the formed all-silica beta molecular sieve is 0.18 mL / g-0.3 mL / g, 0.198 mL / g, 0.20 mL / g, 0.21 mL / g, 0.22 mL / g, 0.23 mL / g, 0.24 mL / g, 0.25 mL / g, 0.26 mL / g, 0.27 mL / g, 0.28 mL / g or 0.29 mL / g.
[0022] In some embodiments, the mechanical strength of the shaped all-silicon β molecular sieve is 50N / cm-300N / cm, for example, 60N / cm, 80N / cm, 90N / cm, 100N / cm, 110N / cm, 120N / cm, 130N / cm, 140N / cm, 160N / cm, 180N / cm, 200N / cm, 230N / cm, 250N / cm or 270 / cm.
[0023] In a second aspect, the present invention provides a method for preparing a shaped all-silicon beta molecular sieve, comprising:
[0024] S1: forming a mixture including a silicon source, a template, a seed crystal and an optional mineralized material to obtain a precursor;
[0025] S2: performing a first drying and crystallization on the precursor to obtain a crystallized product.
[0026] In some embodiments, the method further comprises:
[0027] S3: post-treating the crystallized product to obtain the formed all-silicon β molecular sieve; preferably, the post-treating includes washing, a second drying and calcining.
[0028] The method provided by the present invention mainly adopts dry gel conversion combined with seed crystal method to prepare binder-free molded all-silicon beta molecular sieve, which requires a low amount of seed crystals, a small amount of templates and is easy to recycle, which is beneficial to reducing the discharge of three wastes. At the same time, the dry gel conversion method has a high product yield and low filtration energy consumption, and can also significantly reduce the preparation cost of existing molded all-silicon beta molecular sieves.
[0029] In some embodiments, the seed crystal is selected from β molecular sieve, and the silicon-aluminum ratio of the seed crystal is greater than or equal to 200, calculated as the molar ratio of SiO2 and Al2O3. In some embodiments, the silicon-aluminum ratio of the seed crystal is 200-2000, for example, 300, 500, 700, 1000, 1200, 1400, 1600 or 1800, calculated as the molar ratio of SiO2 and Al2O3.
[0030] In some embodiments, in the mixture, the silicon source is calculated as SiO2, and the molar ratio of the template to the silicon source is 0.1-0.25, for example, 0.11, 0.115, 0.12, 0.125, 0.13, 0.135, 0.14, 0.145, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24 or any value therebetween.
[0031] In some embodiments, the silicon source is calculated as SiO2, and the molar ratio of the template to the silicon source is 0.1-0.15.
[0032] In some embodiments, the mixture consists of a silicon source, a template, a seed crystal, and optionally a mineralizer.
[0033] In some embodiments, the silicon source is selected from one or more of solid silica gel powder, silica sol and water glass. In some embodiments, the mass of Al element in the silicon source is less than 0.15%.
[0034] In some embodiments, the template is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetraethylammonium bromide, tetrapropylammonium hydroxide and tetrapropylammonium bromide.
[0035] In some embodiments, the mineralizer is NaOH and / or KOH.
[0036] In some embodiments, in the mixture, the silicon source is calculated as SiO2, and the molar ratio of water to the silicon source is 2.5-15, for example, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or any value therebetween.
[0037] In some embodiments, in the mixture, the silicon source is calculated as SiO2, and the molar ratio of the seed crystal to the silicon source is 0.01-0.1, for example, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or any value therebetween.
[0038] In some embodiments, in step S2, an organic amine may be added during crystallization. In some embodiments, the organic amine is selected from one or more of ethylenediamine, triethylamine and n-butylamine.
[0039] In some embodiments, the molar ratio of the organic ammonium to the silicon dioxide in the mixture is 0.01-0.1.
[0040] In some embodiments, in step S2, the crystallization time is 12h-144h, for example, 24h, 36h, 48h, 60h, 72h, 84h, 96h, 120h, 140h or any value therebetween. In some embodiments, in step S2, the crystallization time is 12h-72h.
[0041] In some embodiments, in step S2, the crystallization temperature is 120°C-160°C, for example, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C or any value therebetween.
[0042] In some embodiments, in step S1, the molding process is selected from a kneading extrusion molding process or a ball rolling molding process.
[0043] In some embodiments, in step S1, the mechanical strength of the precursor after molding is 100N / cm-300N / cm.
[0044] In some embodiments, in step S2, the first drying temperature is 20°C-80°C.
[0045] In some embodiments, in step S2, the absolute pressure of the first drying is 0.01 MPa-0.1 MPa.
[0046] In some embodiments, in step S3, washing is performed using one or more solutions selected from aqueous ammonium nitrate solution, aqueous ammonium acetate solution, aqueous citric acid solution and water.
[0047] In some embodiments, in step S3, the second drying temperature is 60°C-120°C, for example, 80°C or 100°C.
[0048] In some embodiments, in step S3, the calcination temperature is 550°C-650°C, for example, 580°C, 600°C or 620°C.
[0049] In a third aspect, the present invention provides the use of the shaped all-silicon beta molecular sieve described in the first aspect or the shaped all-silicon beta molecular sieve prepared by the preparation method described in the second aspect as an adsorbent, especially a volatile organic compound adsorbent.
[0050] In some embodiments, the volatile organic compounds include C3-C 12 Alkanes, alkenes and cycloalkanes, C1-C6 low-carbon alcohols and aldehydes.
[0051] In some embodiments, the volatile organic compounds include C3-C6 alkanes or C7-C 10 alkanes, such as one or more of n-butane, n-hexane or cyclohexane.
[0052] Compared with the prior art, the present invention has the following excellent effects:
[0053] (1) The preparation method of the present invention combines dry gel conversion and seed method to prepare binder-free molded all-silicon β molecular sieve in one step, and the crystallization precursor is formed to reduce the energy consumption of powdered molecular sieve filtration, while avoiding the subsequent addition of binder. The yield of the product is close to 100%. The addition of a small amount of seed provides crystal nuclei, reduces the amount of template added in the prior art, and greatly reduces the preparation cost of the current molded all-silicon β molecular sieve. At the same time, the molecular sieve product obtained by the present invention has excellent performance, uniform product size, and a flaky and staggered micromorphology. The specific surface area of the prepared molded all-silicon β molecular sieve is better than that of the prior art.
[0054] (2) The preparation method of the present invention can adjust the gel state in the crystallization precursor by adding a variety of silicon sources and templates, so that the molecular sieve precursor can be formed in one step. The mixing and kneading method of extruding strips or rolling balls can make the solid materials mixed evenly. These two technologies are existing mature processes and are conducive to industrial scale-up.
[0055] (3) The binder-free shaped all-silicon β molecular sieve of the present invention has a large adsorption capacity and good hydrophobicity when used in the treatment of volatile organic compounds, and can be stably regenerated multiple times, thus having good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is the XRD diagram of the molded all-silicon β molecular sieve of Example 1 of the present invention.
[0057] Figure 2 This is a SEM image of the molded all-silicon β molecular sieve of Example 1 of the present invention.
[0058] Figure 3 This is a TEM image of the molded all-silicon β molecular sieve of Example 1 of the present invention. DETAILED DESCRIPTION
[0059] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0060] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0061] The present invention will be described in detail below through examples.
[0062] In the present invention, the specific surface area and pore volume of the catalyst are both well-known in the art and can be tested using methods and instruments known in the art. Specifically, the ASAP2020M physical and chemical adsorption instrument of the American Micromeritics Instrument Company was used, vacuumed before measurement, and treated at 300°C for 2 hours to remove impurities attached to the surface of the sample, and then high-purity N2 was adsorbed at low temperature of liquid nitrogen to obtain the adsorption / desorption curve of the catalyst powder. The specific surface area was calculated by the BET method, and the pore volume was calculated according to the BJH method.
[0063] In the present invention, the mechanical strength of the catalyst is a well-known meaning in the art and can be tested using methods and instruments known in the art. Specifically, the catalyst strength is measured using a DLⅢ intelligent particle strength tester produced by Dalian Chemical Research and Design Institute, and the measurement is performed 22 times, and the maximum and minimum values are removed to obtain the average value.
[0064] In the present invention, XRD uses a Bruker D-8Advance X-ray diffractometer, with Cu K radiation as the radiation source. Graphite monochromator, tube voltage 40kV, tube current 40mA, small angle diffraction range is 5°-50°.
[0065] In the present invention, the microscopic morphology, structure and grain size of the sample are analyzed using an XL30E scanning electron microscope produced by FEI Company of the United States, with a magnification of 20,000 to 40,000 times and an acceleration voltage of 50V-30kV.
[0066] In the present invention, the chemical composition of the sample, ie, the silicon-aluminum ratio, is measured by an X-ray fluorescence spectrometer, the instrument model being Bruker S4 Pioneer.
[0067] In the present invention, high-resolution transmission electron imaging (HR-TEM) is performed on a Tecnai20S-Twin transmission electron microscope produced by FEI Company of the United States, with an acceleration voltage of 200 kV.
[0068] In the present invention, the water content is measured using a water content meter (AND MF50) with an end point temperature of 120°C.
[0069] In the present invention, the VOCs adsorption performance of the material is tested by a self-built evaluation device, which mainly includes a constant temperature device, a gas flow control, an organic gas generator and an adsorption tube. The inert gas carries the volatile organic matter out in the form of bubbles and enters the adsorption column in a bottom-in-top-out manner. The outlet tail gas is detected by online chromatography (FID detector), and the test condition of the online chromatography is automatic injection every 10 minutes.
[0070] Example 1
[0071] Preparation of all-silicon β molecular sieve:
[0072] (1) High-silicon β molecular sieve powder (seed crystal silicon-aluminum ratio 200), silica gel powder, silica sol, 35% tetraethylammonium hydroxide aqueous solution, and tetraethylammonium bromide solid were mixed and kneaded into 3 mm strips, wherein the molar ratio of high-silicon β molecular sieve powder: silica gel powder: silica sol was 5:90:10 based on silicon dioxide, and TEA + / SiO2=0.13, tetraethylammonium hydroxide:tetraethylammonium bromide (molar ratio)=1:4.
[0073] (2) The solid was dried at 35°C until the water content was 10%-20% and then placed in a rotary crystallization reactor at a crystallization temperature of 140°C for 72 hours.
[0074] (3) After crystallization, the molten silicon β molecular sieve is directly washed three times with a 10% ammonium acetate solution, and then washed twice with an aqueous solution, and then dried and calcined at 580° C. to obtain a molded all-silicon β molecular sieve.
[0075] The partial characterization and evaluation results of the formed all-silicon β molecular sieve are shown in Table 1 and Figure 1-3 shown.
[0076] Figure 1 The XRD diagram of the formed all-silicon β molecular sieve of Example 1 of the present invention is shown in FIG. Figure 1 It can be seen that the product synthesized in this example has characteristic diffraction peaks at 7.7° and 22.5°, belonging to β molecular sieve, and the silicon-aluminum ratio measured by XRF is 1226, so the product belongs to all-silicon β molecular sieve;
[0077] Figure 2 This is a SEM image of the formed all-silicon β molecular sieve of Example 1 of the present invention. Figure 2 It can be seen that the all-silicon β molecular sieve product synthesized in this example has uniform size, and its microscopic morphology is flaky and staggered growth;
[0078] Figure 3 This is a TEM image of the formed all-silicon β molecular sieve of Example 1 of the present invention. Figure 3 It can be seen that the all-silicon β molecular sieve synthesized in this example has small grains, belongs to the nanometer scale, and has a regular pore structure. Adsorption performance test:
[0079] The VOCs adsorption performance of the material is tested by a self-built evaluation device.
[0080] The adsorption test conditions are: molded adsorbent, filling volume 100mL, temperature 35℃, diluent nitrogen, volume space velocity 30h -1 , n-butane inlet concentration 2.96×10 6 mg / m 3 , n-hexane inlet concentration 1.59×10 6 mg / m 3 , cyclohexane inlet concentration 9.00×10 5 mg / m 3 The equilibrium adsorption capacity (mg / g) refers to the ratio of the mass of the material adsorbed to the mass of the fresh adsorbent when the outlet exhaust concentration is the same as the inlet concentration.
[0081] The adsorption performance test results are shown in Table 2.
[0082] Example 2
[0083] The difference from Example 1 is that the crystallization temperature is 130° C. The characterization results are shown in Table 1.
[0084] Example 3
[0085] The difference from Example 1 is that the crystallization temperature is 120° C. The characterization results are shown in Table 1.
[0086] Example 4
[0087] The difference from Example 1 is that TEA + / SiO2=0.16, and the characterization results are shown in Table 1.
[0088] Comparative Example 1
[0089] The difference from Example 1 is that during the preparation, sodium aluminate is added to the crystallization precursor in a SiO2 / Al2O3 molar ratio of 25:1. The characterization results are shown in Table 1.
[0090] Comparative Example 2
[0091] The difference from Example 1 is that the crystallization temperature is 170° C. The characterization results are shown in Table 1.
[0092] Comparative Example 3
[0093] The difference from Example 3 is that no seed crystal is added. The characterization results are shown in Table 1.
[0094] Comparative Example 4
[0095] The difference from Example 1 is that the adsorption material is activated carbon, and its characterization and evaluation results are shown in Table 2.
[0096] Comparative Example 5
[0097] The difference from Example 1 is that the adsorption material is ZSM-5 molecular sieve, and its characterization and evaluation results are shown in Table 2.
[0098] Comparative Example 6
[0099] The difference from Example 1 is that the adsorption material is a molded HY molecular sieve, wherein the silicon-aluminum ratio of HY is 4.8, and the mass ratio of the molecular sieve to the alumina binder is 7:3. The characterization and evaluation results are shown in Table 2.
[0100] Comparative Example 7
[0101] The difference from Example 1 is that the adsorption material is a β molecular sieve with a silicon-aluminum ratio of 25, and the mass ratio of the molecular sieve to the alumina binder is 7:3. The characterization and evaluation results are shown in Table 2.
[0102] Table 1
[0103]
[0104] Table 2
[0105]
[0106] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A shaped all-silicon beta molecular sieve, wherein: The crystals of the all-silicon beta molecular sieve have a flaky morphology, and the crystal size is less than or equal to 300 nm. The specific surface area of the all-silicon beta molecular sieve is 550 m 2 / g-750m 2 / g.
2. The shaped all-silicon β molecular sieve according to claim 1, characterized in that: The flake morphology includes a staggered growth flake morphology; and / or The thickness of the crystal is less than or equal to 50 nm; and / or The size of the crystal of the formed all-silicon beta molecular sieve in the length direction is 20nm-300nm; the size of the crystal of the all-silicon beta molecular sieve in the width direction is 20nm-300nm; and / or The micropore volume of the formed all-silicon beta molecular sieve is 0.18 mL / g-0.3 mL / g; and / or The mechanical strength of the molded all-silicon beta molecular sieve is 50N / cm-300N / cm.
3. A method for preparing a molded all-silicon beta molecular sieve, comprising: S1: forming a mixture including a silicon source, a template, a seed crystal and an optional mineralized material to obtain a precursor; S2: performing a first drying and crystallization on the precursor to obtain a crystallized product.
4. The preparation method according to claim 3, characterized in that: The method further comprises: S3: post-treating the crystallized product to obtain the formed all-silicon β molecular sieve; preferably, the post-treating includes washing, a second drying and calcining.
5. The preparation method according to claim 3 or 4, characterized in that: The seed crystal is selected from β molecular sieve, and the silicon-aluminum ratio of the seed crystal is greater than or equal to 200, preferably 200-2000, calculated by the molar ratio of SiO2 and Al2O3.
6. The preparation method according to any one of claims 3 to 5, characterized in that: In the mixture, the silicon source is calculated as SiO2, and the molar ratio of the template to the silicon source is 0.1-0.25, preferably 0.1-0.
15.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The mixture consists of a silicon source, a template, a seed crystal and an optional mineralizer; Preferably, the silicon source is selected from one or more of solid silica gel powder, white carbon black, silica sol and water glass, and the mass of Al element in the silicon source is preferably less than 0.15%; Preferably, the template is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetraethylammonium bromide and tetrapropylammonium bromide; Preferably, the mineralizer is NaOH and / or KOH; Preferably, in the mixture, the silicon source is calculated as SiO2, the molar ratio of water to the silicon source is 2.5-15, and the molar ratio of the seed crystal to the silicon source is 0.01-0.
1.
8. The preparation method according to any one of claims 3 to 7, characterized in that: In step S2, the crystallization time is 12h-144h, preferably 12h-72h; and / or the crystallization temperature is 120°C-160°C; and / or In S2, after the precursor is first dried, the mass content of water in the precursor is 5%-30%, preferably 10%-20%.
9. The preparation method according to any one of claims 3 to 8, characterized in that: In step S1, the molding process is selected from a kneading extrusion molding process or a ball molding process, and preferably, the mechanical strength of the precursor after molding is 100N / cm-300N / cm; and / or In step S2, the temperature of the first drying is 20°C-80°C, and the absolute pressure of the first drying is 0.01MPa-0.1MPa; and / or In step S3, washing is performed using one or more solutions selected from aqueous ammonium nitrate solution, aqueous ammonium acetate solution, aqueous citric acid solution and water; and / or In step S3, the second drying temperature is 60°C-120°C, and the calcining temperature is 550°C-650°C.
10. Use of the shaped all-silicon beta molecular sieve according to claim 1 or 2 or the shaped all-silicon beta molecular sieve prepared by the preparation method according to any one of claims 3 to 8 as an adsorbent, especially an adsorbent for volatile organic compounds.
Citation Information
Patent Citations
BEA type binder-free dewatering silica-rich zeolite adsorbent and preparation method thereof
CN101757889A
Method for synthesizing full-silicon beta zeolite with small crystal grains
CN101863490A
Method for synthesizing all-silicon Beta zeolite molecular sieve by sodium-free solvent-free route
CN108264056A
All-silicon Beta molecular sieve synthesis process and all-silicon Beta molecular sieve prepared by all-silicon Beta molecular sieve synthesis process
CN113636566A
Beta zeolite molecular sieve and preparation method thereof
CN115991483A